Balancing Agricultural Development and Conservation: Community Perspectives on Land Use Challenges in Lebong Regency, Indonesia - Alfarabi, Alfarabi; Yogopriyatno, Jatmiko; Sartika, Sartika; Puspitasari, Venti (Universitas Teuku Umar, 2025)
This research analyzes community perspectives on agriculture, plantation, and food programs in Lebong Regency, with a particular focus on the Double Cropping Season (MT2) program. This research draws upon three interconnected theoretical frameworks: Political Ecology Framework for analyzing power relations in environmental access, Sustainable Livelihoods Approach for examining rural community adaptations, and Adaptive Co-Management Theory for analyzing collaborative natural resource management. Using a mixed-method approach, the study was conducted in seven sub-districts with 100 respondents selected through cluster random sampling. The findings reveal varying levels of community satisfaction, with satisfaction indices reaching 76 in three main sub-districts and 66 in four companion sub-districts. 78% of the community supports program continuation with noted improvements. Key implementation challenges include inequitable land ownership structures, where the majority are tenant farmers, agricultural land conversion, and land conflicts related to conservation areas that cover 69.89% of Lebong Regency. Analysis through these theoretical frameworks reveals that successful agricultural development in Lebong requires fundamental changes in power distribution, institutional support, and program implementation approaches. The research recommends establishing a multi-stakeholder governance platform, modifying the MT2 program to focus on agricultural intensification, and adopting more flexible management approaches to balance agricultural productivity with conservation needs.